Reintervention, PROMs, and Factors Influencing PROMs Following Surgery for de Quervain's Tenosynovitis - Zamri, Meryam; Lans, Jonathan; Eberlin, Kyle R.; Garg, Rohit; Jupiter, Jesse B.; Chen, Neal C. (Journal of Hand and Microsurgery, 2021)
Objective The aims of this study are to describe and identify the factors that influence patient reported outcomes following surgery of de Quervain's tenosynovitis. The secondary objective is to report the rate of reintervention following surgery of de Quervain's tenosynovitis.Patients and Methods Outcomes using the numerical rating scale (NRS) for pain, Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH), Patient-Rated Wrist Evaluation (PRWE), the Patients Reported Outcome Measurement Information System Pain Interference (PROMIS PI), and a custom de Quervain's questionnaire were obtained. A multivariable linear regression analysis was performed to identify independent factors associated with patient-reported outcomes.Results Seventy-six patients who underwent de Quervain's release participated. The average age was 52.8 years (95% confidence interval: 49.6–56.1) and median follow-up age was 7.0 years (interquartile range [IQR]: 4.3–12.0). Outcomes were: NRS of pain was 0 (IQR: 0.0–3.0), the median QuickDASH was 6.82 (IQR: 0.00–28.41), the median PRWE score was 4.0 (IQR: 0.00–18.50), and the median PROMIS PI score was 43.90 (IQR: 38.70–53.90). Eighteen (23.7%) of the patients reported pain with thumb activities, four of whom had a reintervention. Additionally, 21 (26.9%) patients reported decreased strength in the thumb compared to the contralateral side, of which two underwent a reintervention. In total, eight patients underwent reintervention of which seven had a second surgery and one had a cortisone injection.Conclusion Roughly 1 in 20 patients following de Quervain's release undergoes reintervention. Patients with high PROMIS PI scores report poor surgical outcomes more frequently. Patients with high PROMIS PI scores report higher NRS pain scores (p < 0.05), higher QuickDASH scores (p < 0.05), and higher PRWE scores (p < 0.05). In practice, careful consideration of PROMIS PI scores and psychosocial factors are recommended before considering reintervention.
Keywords: tenosynovitis; de Quervain stenosing tenosynovitis; de Quervain disease; treatment failure; recurrence; follow-up studies